2001
DOI: 10.1038/sj.gt.3301541
|View full text |Cite
|
Sign up to set email alerts
|

Observed incidence of tumorigenesis in long-term rodent studies of rAAV vectors

Abstract: Gene therapy using recombinant adeno-associated virus vectors (rAAV) is generally considered safe. During the course of a study designed to determine the long-term efficacy of rAAV-mediated gene therapy initiated in newbornRecombinant adeno-associated virus (rAAV) vectors are generally considered safe. No side-effects have been reported in the many in vivo studies designed to assess the efficacy of rAAV vectors.1 Wild-type AAV (wtAAV) is not associated with any disease and the virus integrates with high freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
192
3
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 281 publications
(205 citation statements)
references
References 13 publications
6
192
3
1
Order By: Relevance
“…In mucopolysaccharidosis type VII mice, Donsanto et al 5,7 discovered an increased incidence of liver tumours after systemic administration of rAAV vectors, a finding supported by specific rAAV genomic integration analyses, and concluded that administration of rAAV could lead to malignant transformation. On the other hand, Bell et al 6 looked at tumour incidence in an ornithine transcarbamylase-deficient mouse model with and without rAAV gene therapy.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In mucopolysaccharidosis type VII mice, Donsanto et al 5,7 discovered an increased incidence of liver tumours after systemic administration of rAAV vectors, a finding supported by specific rAAV genomic integration analyses, and concluded that administration of rAAV could lead to malignant transformation. On the other hand, Bell et al 6 looked at tumour incidence in an ornithine transcarbamylase-deficient mouse model with and without rAAV gene therapy.…”
Section: Resultsmentioning
confidence: 98%
“…4 Concerns have also been raised by several in vivo studies regarding the possibility of pro-oncogenic events arising from recombinant adeno-associated virus (rAAV) vectormediated gene transfer to hepatocytes, concerns that are supported by vector integration site analyses. [5][6][7][8] Insertional mutagenesis (IM) is a risk associated with the transposition of genetic material. The ectopic integration of DNA arising from the use of integrating viral vectors may disrupt chromatin or gene structure, thereby altering gene transcription, regulation and/or coding sequences.…”
Section: Introductionmentioning
confidence: 99%
“…7 Concerns surrounding the latter findings have been allayed, in part, by attribution of the abnormal pathology to the long-term survival of a mouse model normally subject to early mortality in the absence of AAV-mediated therapeutic gene delivery. 8 Immune responses against AAV, although mild and noninflammatory, have been documented. Of the known AAV serotypes, antibodies against serotype 2 appear at the highest frequencies (ie, 30-90% of human populations), while those against serotypes 1 and 5 are observed less often.…”
Section: Introductionmentioning
confidence: 99%
“…31 Vector integration in tumors was shown. In at least some of the cases, integration occurred in a microRNA locus on mouse chromosome 12.…”
Section: Genomic Integrationmentioning
confidence: 99%